2003
DOI: 10.1182/blood-2003-01-0180
|View full text |Cite
|
Sign up to set email alerts
|

Memory B cells producing somatically mutated antiphospholipid antibodies are present in healthy individuals

Abstract: Antiphospholipid antibodies (aPLs) are associated with thrombosis and recurrent abortions during autoimmune pathologies, but they are also produced in healthy individuals and during infectious diseases. To analyze the possible links between physiologic and pathologic aPLs, it is of importance to characterize normal aPL production. We took advantage of the known tropism of Epstein-Barr virus (EBV) for B cells in general, and memory B cells in particular, during primary infectious mononucleosis (IMN) in 3 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 36 publications
0
29
0
2
Order By: Relevance
“…54 Support for the identification of antiphospholipid antibodies as natural antibodies comes from the observation that healthy persons without APS can have memory B cells that produce antiphospholipid antibodies. 57 In several elegant studies, Fleming et al have shown that natural anti-␤ 2 GPI antibodies are involved in complement-mediated mesenteric ischemia/reperfusioninduced injury. 58,59 In addition, there are also indications that natural antiphospholipid antibodies are involved in acute graft rejection after renal transplantation.…”
Section: The Etiology Of Autoantibodies Against ␤ 2 Gpimentioning
confidence: 99%
“…54 Support for the identification of antiphospholipid antibodies as natural antibodies comes from the observation that healthy persons without APS can have memory B cells that produce antiphospholipid antibodies. 57 In several elegant studies, Fleming et al have shown that natural anti-␤ 2 GPI antibodies are involved in complement-mediated mesenteric ischemia/reperfusioninduced injury. 58,59 In addition, there are also indications that natural antiphospholipid antibodies are involved in acute graft rejection after renal transplantation.…”
Section: The Etiology Of Autoantibodies Against ␤ 2 Gpimentioning
confidence: 99%
“…According to the recent scientific literature, sequence analysis of antibody genes using Chang and Casali's method 10 is utilized most widely to ascertain the involvement of antigenic selection in disease pathogenesis in cases of different autoimmune disorders [12][13][14][15][16][17] and lymphomas. [18][19][20][21][22][23][24][25] However, Chang and Casali's method does not consider the differences in the intrinsic mutability of various regions of antibody genes.…”
Section: Abstract: Immunoglobulin Variable Regions; Somatic Mutation;mentioning
confidence: 99%
“…The baculovirus expression system has been used for basic research to analyze the molecular basis of specificity, 21,22,41,52 autoimmunity 32,33,36,39,41,42 or the function of intact antibodies or of isolated immunoglobulin domains. 18,40,[43][44][45][46] It is very easy and fast to generate recombinant viruses expressing H or L bearing specific mutations and to determine the impact of these mutations on the specificity or activity of a given antibody.…”
Section: Biological Activities Of Recombinant Antibodies Produced In mentioning
confidence: 99%
“…21,22,41 This strategy has been successfully used to analyze the catalytic activity of the 6D9 monoclonal antibody and the specificity of the PAC1 antibody that binds to the integrin αII b β3 on activated platelets. 18,52 Universal expression cassettes have also been designed either to directly clone the VH and VL domains of antibodies expressed by murine cells or by human B-cells isolated from patients 26,32,33,36,39 or to convert scFv or Fab fragments selected from phage-display libraries into an intact fully human or chimeric IgG. 29,34,35,37,38,42 The aim of many of these experiments was to isolate, characterize and validate antibodies for further therapeutic applications in the treatment of human diseases such as hemolytic disease of newborn, 31 cancer 23,27,[56][57][58] and infectious diseases, with the selection of neutralizing antibodies against hemorrhagic fever viruses (e.g., hantaan, Puumala viruses), 34,35,72 human cytomegalovirus, 37 influenza virus 38 or prion protein.…”
Section: Biological Activities Of Recombinant Antibodies Produced In mentioning
confidence: 99%
See 1 more Smart Citation